A Flexible Regimen of Combination Antihypertensive Therapy for Lower Blood Pressure to the Lower Target Level. Viewpoint of Cardiologist and Clinical Pharmacologist - S. R. Gilyarevskiy; M. V. Golshmid; G. Yu. Zaharova; I. M. Kuzmina; I. I. Sinitsina (Рациональная фармакотерапия в кардиологии, 2019)
Modern tactics of antihypertensive therapy with fixed dose combination or with free combinations of antihypertensive drugs are reviewed in the article. The evidence that a flexible regimen of combination antihypertensive therapy is more reasonable in the modern treatment of arterial hypertension is presented. The question of the characteristics of hypertensive patients in whom lowering blood pressure to lower target levels may be useful to improve the prognosis is discussed considering the results of the analysis of data on participants in a randomized clinical trial SPRINT. Approaches to reducing the incidence of adverse events caused by antihypertensive therapy in such patients in general and in elderly and senile patients who have not only a higher likelihood of achieving advantages of more intensive antihypertensive therapy regimens for influencing the prognosis, but also a higher risk of complications, due to therapy are considered. The problem of less high efficacy of using replicated antihypertensive drugs (generics) compared to the original drugs is discussed.